Development of learning media and online test based smartphone android in physics learning on work and energy topic - Muh Makhrus; Joni Rokhmat; Kosim Kosim; Ahmad Harjono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Technological developments affect the development of learning. Along with this, the development of covid throughout the world makes learning required to present creative learning with innovative media. This research aims to develop learning media and online HOTS tests based on smartphone android in physics learning. This research using a procedural model. The analysis in this development research uses ideal standards to analyze the validation or feasibility of the physics learning media. The media and online HOTS tests were analyzed by 4 experts in the field of physics education. The results of the analysis show that the learning media is categorized as feasible or valid based on three categories, namely in terms of the media display, software, and material.